2021
DOI: 10.25259/sni_827_2021
|View full text |Cite
|
Sign up to set email alerts
|

Malignant ossifying fibromyxoid tumor of the brain treated with post-operative fractionated stereotactic radiation therapy: A case report and literature review

Abstract: Background: Ossifying fibromyxoid tumor (OFMT) is a rare musculoskeletal soft-tissue neoplasm of uncertain histogenesis most frequently occurring in the lower extremities. Conventionally, considered benign, these tumors are often managed by surgical resection followed by surveillance. However, malignant OFMTs with an increased propensity for local recurrence and distant metastasis have been recently identified, and the role of adjuvant therapy in these more aggressive cases is unclear. Case Description: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…OFMTs resemble other mesenchymal tumors microscopically; therefore, immunostaining for molecular markers is essential for diagnosis [ 13 ]. The peripheral rim of bone tissue and positive S-100 immunostaining are the best predictors of typical OFMTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OFMTs resemble other mesenchymal tumors microscopically; therefore, immunostaining for molecular markers is essential for diagnosis [ 13 ]. The peripheral rim of bone tissue and positive S-100 immunostaining are the best predictors of typical OFMTs.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited literature regarding adjuvant radiation and chemotherapy in aggressive OFMTs. Our literature review found two OFMT cases where radiation therapy was used to treat the tumor and prevent local recurrence [ 13 , 15 ]. In these case reports, after using adjuvant radiation therapy, one patient was disease-free for more than 5 ½ years after resection, and the second was disease-free for more than 18 months on the routine follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…T 1 MR image of a brain with a fibromyxoid tumor (a) without contrast (b) with contrast . Reproduced with permission from ref . Copyright 2021 Surgical Neurology International.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we present the narrative of two clinicopathologically unconventional cases of malignant OFMT originally misclassified as highgrade osteosarcoma, including one of four reported cases primary to the brain which also harbored a heretofore undescribed CREBZF::PHF1 fusion. [1][2][3] Pitfalls inherent to the differential diagnosis are discussed.…”
Section: Introductionmentioning
confidence: 99%